Strength characteristic of soft soil reinforced with coir fibres - Wan Hasmida, Wan Hassan (2010)
Use of natural fibres in civil engineering construction practice is often advantageous as they are cheap, locally available, biodegradable, and friendly.Among the available natural fibres, coir fibre especially coconut coir fibre is produced in large quantities in Malaysia and others country such as India,Philippines, Indonesia and so on. The coir fibres also have better mechanical properties in tensile strength. For this research the soil samples are taken about 4 in depth from ground surface at Kampung Beruas, Pekan. The tests were conducted to determine engineering properties of soil samples such as classification, Standard Proctor Compaction Test, Unconsolidated Undrained Test (UUT) and Oedomoter Consolidation Test. The soil was classified as clay with high plasticity, having liquid limit, plastic limit, plastic index and shrinkage limit of 72.0%, 31.36%, 40.64%, and 7.86% respectively and specific gravity was 2.51. Maximum dry density (MDD) and optimum moisture content (OMC) from compaction test were used as the basis in preparing sample for Undrained Unconsolidated Test (UUT). The soil samples reinforced with coir fibres of different sizes and content were test to determine the compaction, strength and the consolidation of soil response due to fibre inclusion and the results were compared with that of unreinforced soils. The results. show that addition of coir fibre with different content (0.25%, 0.50%, 0.75%, 1.0%) and length (15 mm, 25 mm, 35 mm, 45 mm) as random reinforcing material increase the compaction and strength of soft soil. The effectiveness of coir fibre in shear strength is 105.68 kPa for 35 mm in fibre length and 0.50% in fibre content. Besides, the MDD and OMC is 16.10 kPa and with 13% which is from 45 mm at 0.50% of fibre length and content. For consolidation the soil after treated produced the less consolidation and decreases the void ratio of the soil samples in stabilized soft soil.